The social setting of correctional centres and general practices: perspectives of correctional officials in Kano State, Nigeria: research - Amali, Sadiq Ewaoda (Acta criminologica, 2018)
This study was conducted in Kano Central and Goron-Dutse prisons to empirically examine the perceptions of correctional officials on correctional centre social setting and general practices in Kano state, Nigeria. The sample comprised both male and female correctional officials in the study area. Questionnaires amounting to 207 were administered to correctional officials in Kano Central and Goron-Dutse prisons. A sample size of 207 was determined using the sample size calculator at a confidence interval of +5, confidence level of 95 percent out of a population of 449 correctional officials. Selected findings reveal that most of the respondents in Kano Central prison (59.8%) stated that infrastructure was adequate compared to only 40.2 percent of correctional officials in Goron-Dutse Prison. This study concludes that the desired rehabilitation can be achieved with concerted efforts by the Nigerian government by providing decent rehabilitation programmes and facilities across the two correctional centres studied with due regard to the fact that there was some level of dissatisfaction by some respondents. This study recommends monthly or quarterly assessment of correctional centre conditions by the Nigerian government.